Development of Technology and Trial Production of Extremely High Resistant Nanoporous Graphite Sealers for Nuclear Reactors - Bondarenko, B.I.; Kozhan, O.P.; Dmіtrіev V.M.; Rjabchuk, V.S.; Stratіvnov Ye.V.; Simeiko, K.V. (Science and Innovation, 2024)
Introduction. As a result of termination of cooperation with Russian Federation, it became necessary to diversify supplying not only nuclear fuel, but also goods and materials for assembly, operation, technical maintenance, and repair of power engineering equipment. Problem Statement. Critically important products include, in particular, gaskets for sealing the plug-type connections of reactor units with water-cooling equipment, for example, ПГВ-1000M steam generators. For the time being, the existing reserves of TEG (thermally expanded graphite) gaskets imported from Russia for upgraded steam generators ПГВ-1000M and ПГВ-213 have been almost exhausted, therefore there is an urgent need for the domestic production of these and other TEG sealers. Purpose. Development of technological framework for manufacturing TEG sealers for the NPP technological equipment. Materials and Methods. Graphite foil of different manufacturers obtained from original natural graphite, conventional methods for measuring the physico-technical characteristics of sealing gaskets. Results. Within the framework of the conducted R&D works, the physical, technical, and physicochemical properties of graphite foils made of natural graphite derivatives by various manufacturers have been established; molds of two standard sizes have been designed and manufactured; the technology for molding the sealers from graphite foil has been tested; specific compression force to obtain the sealers of given density has been determined; specific compression strength of the obtained gaskets has been established. Conclusion. The obtained results can be used for developing a new pilot manufacture of TEG sealing gaskets by domestic corporations.